Innovation in Family Literacy Learning Through Habituation at the Raudhatul Athfal Creative House Wadas Kelir - Zubaedah, Siti; Hafidz, Nur; Nurbaiti, Amalia (Annual Conference on Islamic Early Childhood Education (ACIECE), 2024)
Literacy habits from an early age have an important role in forming a critical and creative mindset in children. This study aims to explore the innovation of Family Literacy Learning applied in Raudhatul Athfal (RA) Rumah Kreatif Wadas Kelir. Through a descriptive qualitative approach, this study identifies innovative strategies that involve the active participation of families in children's literacy activities at home and school. The results showed that the results of this study indicate that the habituation of literacy in the family and RA Creative House Wadas Kelir, Karangklesem, South Purwokerto, Banyumas conducted through family literacy learning innovations in RA Creative House Wadas Kelir which includes (1) regular refraction in the form of borrowing books in the library, Read Aloud, and Reward; (2) spontaneous habituation in the form of Recall and active children reading books themselves; and (3) exemplary habituation in the form of Read Aloud and teachers reading books. Family Literacy Learning Innovation in Ra Wadas Kelir makes a significant contribution to the development of early childhood literacy and becomes a relevant learning model to be applied in other educational institutions